1951
DOI: 10.1007/bf02612206
|View full text |Cite
|
Sign up to set email alerts
|

The flavor problem of soybean oil. VIII. Linolenic acid

Abstract: Summary Circumstantial evidence has long pointed to linolenic acid as the unstable precursor of “reversion” flavors in soybean oil. Direct evidence has now been obtained from two sources: a) A qualitative study of the flavors after storage of soybean oil in which the linolenic acid content has been significantly lowered by furfural extraction, and b) organoleptic identification studies of stored soybean oil, stored cottonseed oil, and a cottonseed oil into whose glyceride structure linolenic acid has been intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0
1

Year Published

1959
1959
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 4 publications
0
40
0
1
Order By: Relevance
“…The five main fatty acids present in soybean seed are palmitic (16:0), stearic (18:0), oleic (18:1), linoleic (18:2), and linolenic (18:3) [6]. The higher linoleic and linolenic acids were reported to lower the shelf-life of the oil due to oxidation of polyunsaturated acids [7,8]. Hence, the soybean industry prefers soybean with lower percentages of linoleic and linolenic acids, and higher percentage of oleic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The five main fatty acids present in soybean seed are palmitic (16:0), stearic (18:0), oleic (18:1), linoleic (18:2), and linolenic (18:3) [6]. The higher linoleic and linolenic acids were reported to lower the shelf-life of the oil due to oxidation of polyunsaturated acids [7,8]. Hence, the soybean industry prefers soybean with lower percentages of linoleic and linolenic acids, and higher percentage of oleic acid.…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1940s, Evans and co-workers began publishing a series of papers on the flavor problems of soybean salad oil. Some of these studies reported that the linolenic acid content of soybean oil was a major source of the flavor problems for this oil (1)(2)(3). In these investigations, "painty" was a primary flavor characteristic in oxidized soybean salad oils that was attributed to the linolenic acid content.…”
mentioning
confidence: 96%
“…Linoleic acid is the precursor of the essential fatty acid arachidonic acid, and when incorcorpated in the diet of monogastric animals, furnishes polyunsaturated tissue fats. The presence of linolenic acid in edible oils is viewed unfavourably, as it gives rise to off-flavours through autoxidation (Dutton et al 1951). Erucic acid, when fed to animals at high levels, has been held responsible for pathological abnormalities (Abdellatif 1972).…”
Section: Introduction Experimentalmentioning
confidence: 99%